Heavy metal ions removal from wastewater using various low-cost agricultural wastes as adsorbents: a survey - Bnar M. Ibrahim (Zanco Journal of Pure and Applied Sciences, 2021)
Toxic heavy metals have an important role in water pollution. Because of their toxicity and non-biodegradability which affects humans, animals, and also plants. Researchers in the field of environment used various heavy metal removal methods, such as ion exchange, precipitation, evaporation, membrane filtration and adsorption. Low cost, high efficiency and easy regeneration make the adsorption process as an effective technique in the heavy metal removal. The purpose of this review is to gather sufficient information about various agricultural waste adsorbents and their removal capacity for heavy metals.